A new scale to assess technostress levels in an Italian banking context: the Work-Related Technostress Questionnaire - Porcari, Desirée Estela; Ricciardi, Emiliano; Orfei, Maria Donata (Frontiers in Psychology, 2023)
Introduction Technostress (TS) represents a multidimensional phenomenon closely related to the pervasive use of information and communication technologies. This study aimed to validate a new psychometric tool for assessing TS in an Italian banking context, the Work-Related Technostress – Questionnaire (WRT-Q). Secondly, we analyzed the role of gender and age in modulating TS manifestations. Methods A sample of 2,586 bank employees (51% females; age: 47.26 ± 8.6) underwent an online survey. Reliability, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), ANCOVA, independent sample t-test, and correlation analyses were performed. Results The WRT-Q consisted of 17 items and a four-factor structure, supported by the following CFA indices: Comparative Fit Index (CFI) = 0.985; Incremental Fit Index (IFI) = 0.985; Goodness of Fit (GFI) = 0.988; Root Mean Squared Error of Approximation (RMSEA) = 0.071; and SRMR = 0.062. A significant difference in TS levels between age classes emerged (p < 0.001) with higher levels in the over 55-year-old subgroup, while no statistically significant difference emerged for gender. Moreover, the whole sample found a significant positive association between age and TS (p < 0.001). Discussion The WRT-Q is a new instrument to measure TS in the workplace, it can contribute to highlighting adverse outcomes in individuals due to a dysfunctional interaction with ICT.